Non-financial rewards for human resource management in technological companies. - Almadana-Abón, Santiago Antonio; Molina-Gómez, Jesús; Mercade-Mele, Pere; Núñez-Sánchez, José Manuel (OmniaScience, 2024)
of total compensation and its relationship to human resource management mediated by the relationship of strategic corporate governance in the technology sector. Design/methodology/approach: A quantitative approach of extrinsic and intrinsic non-financial rewards, human resource management and strategic management of the company has been carried out. To obtain the necessary data, self-administered questionnaire were used. The results obtained from a sample of 97 human resource managers in the technology sector proves the causal relationship between each type of non-financial reward and human resource management, as well as its link to the strategic management. Findings: Using Partial Least Squares Structural Equation Model (PLS-SEM), significant relationships occur between human resource management and strategic management, followed by the relationship between human resource management and intrinsic rewards. A significant relationship exists between human resource management and direct and indirect intrinsic rewards through strategic management. In turn, only an indirect relationship exists between human resource management and extrinsic non-financial rewards through strategic management, but there is no direct relationship. Originality/value: These findings are highly important for human resource management, since it could allow the development of new compensation strategies with non-financial rewards under strategic management helping technology companies to generate competitive advantage by means of the same.
El texto analiza la relación entre la compensación total y la gestión de recursos humanos (HRM), centrándose en cómo esta relación es mediada por la gobernanza corporativa estratégica, específicamente en el sector tecnológico. Enfoque: El estudio utiliza un método cuantitativo, examinando tanto las recompensas no financieras extrínsecas (externas) como intrínsecas (internas), junto con la gestión de recursos humanos y la gestión estratégica de la empresa. Los datos se obtuvieron a través de cuestionarios autoadministrados aplicados a 97 gerentes de recursos humanos en el sector tecnológico, lo que permitió establecer las conexiones causales entre los tipos de recompensas no financieras y HRM, así como su vínculo con la gestión estratégica. Hallazgos principales: Mediante el uso de modelos de ecuaciones estructurales de mínimos cuadrados parciales (PLS-SEM), se encontraron relaciones significativas entre la gestión de recursos humanos y la gestión estratégica, además de una relación entre HRM y las recompensas intrínsecas (tanto directas como indirectas). El estudio también reveló que la relación entre HRM y las recompensas extrínsecas es únicamente indirecta a través de la gestión estratégica, sin un vínculo directo. Valor: Estos resultados son especialmente importantes para la gestión de recursos humanos, ya que sugieren nuevas estrategias de compensación utilizando recompensas no financieras dentro del marco de la gestión estratégica, lo que podría ayudar a las empresas tecnológicas a desarrollar una ventaja competitiva.
Keywords: Gestión de recursos humanos; Motivación en el trabajo; Total compensation; Intrinsic rewards; Human resources management; strategic management; Non-financial rewards